Where the light goes [compact disc] - Shires, Amanda; Wattenberg, Gregg (Atlantic, 2023)
Where the Light Goes is the fifth studio album by American rock band Matchbox Twenty, released on May 26, 2023, by Atlantic Records. On March 17, 2023, the band released the first single from the album, "Wild Dogs". It is the band's first album in over a decade since North in 2012.